Interest in disinterestedness in the epidemiology of health systems and services - Hugo Spinelli (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
This article intends to critique of the cultural authority of the medical sciences, opening up a discussion on its publicization from a political standpoint. At the same time, from a more technical standpoint, it proposes the implementation of an epidemiology of health systems and services. Based on Pierre Bourdieu's concept of interest in disinterestedness and Joseph Gusfield's notion of the cultural authority of public problems, it analyzes why epidemiological information is so rarely used in the evaluation and monitoring of clinical, population, institutional, and territorial practices. That is, why does the dominant culture of decision making eschew epidemiological information? Within this conceptual framework, a body of documental evidence is analyzed that sheds light on the weak scientific basis that upholds or that has underpinned certain practices in the health field at different historical moments. The discussion is organized around three major themes: assistentialist professional practice, medication, and biomedical technologies.